Precocious puberty in male wild boars: a possible explanation for the dramatic population increase in Germany and Europe - Maistrelli,Claudia; Hüneke,Hanna; Langeheine,Marion; Keuling,Oliver; Siebert,Ursula; Brehm,Ralph (PeerJ, 2021)
Background The wild boar population in Europe is steadily growing, one of the reasons for this increase probably being the high reproductive potential of this large mammal. Population management is important to stabilise wild boar numbers and a great deal of attention is focusing on the reasons, which might contribute to the high reproductive rates. Understanding the timing of puberty attainment provides information required for proper management practices. Knowledge of the earliest expected time of sexual maturation in male wild boars is limited, research being mostly focused on females. Previous hunting references indicate that sexual maturity in males occurs in the second year after birth. In contrast, male domestic pigs become sexually mature from about seven months of age. Thus, aims of this study were to investigate (1) whether there is a physiological ability for reproduction also in male wild boars of a younger age and (2) whether the body weight of wild boar males has a more important role than age in driving the maturation of the testis. Methods Male wild boar individuals were sampled during hunting drives in the eastern part of Lower Saxony in Germany. Testes with epididymides from 74 males were collected and prepared for histological examination and immunohistochemistry. The reproductive status could be ascertained based on development/occurrence of different germ cell populations using histology and based on the immunohistochemical detection of the anti-Müllerian hormone and androgen receptor. Results In this study, male wild boars aged nine to ten months already passed puberty and were able to reproduce if they had reached the appropriate body condition of about 29 kg dressed weight. Immunopositivity to the anti-Müllerian hormone in Sertoli cells was evident only in prepubertal animals and decreased with the onset of puberty. No immunoreaction was evident at postpuberty. The androgen receptor was detected in Sertoli cells, peritubular cells and Leydig cells, surprisingly already in Sertoli cells of prepubertal wild boars as well depending on body weight. Moreover, two-thirds of young males aged about ten months were precociously reproductively mature, showing histologically the presence of spermatozoa in testes and epididymides. Conclusions As piglets are mostly born in spring, also these young male individuals could target the heat of female wild boars in the winter months, resulting in the observed population increase. Therefore, a reduction in wild boar numbers should also focus on piglets of both sexes.
Keywords: Androgen receptor; Anti-Müllerian hormone; Male reproduction; Precocity; Puberty; Spermatogenesis; Sus scrofa